2004
DOI: 10.1021/ac035249o
|View full text |Cite
|
Sign up to set email alerts
|

Developments toward a Microfluidic System for Long-Term Monitoring of Dynamic Cellular Events in Immobilized Human Cells

Abstract: A microfluidic system for long-term real-time monitoring of dynamic cellular events of immobilized human cells was investigated. The luciferase reporter gene activity in the reporter cell line HFF11, based on HeLa cells, was used as the model system. The cells were immobilized on silicon flow-through microchips and continuously supplied with a cell medium at 2 microL/min while maintaining the chip at 37 degrees C. The HFF11 cell line was designed for high-throughput screening of ligands for seven-transmembrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 15 publications
0
35
2
Order By: Relevance
“…7,[15][16][17][18][19][20][21][22][23][24][25] Very recently, a transparent chamber with an integrated heater 24 and flow equalization structure 26 has been shown to support a stable cell culture for several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…7,[15][16][17][18][19][20][21][22][23][24][25] Very recently, a transparent chamber with an integrated heater 24 and flow equalization structure 26 has been shown to support a stable cell culture for several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations of adhesive properties of biological cells on chip have shown that there are no negative influences on the cellular conditions and behavior [347]. Other studies have shown that PDMS-based microfluidic systems can maintain normal cell viability for several weeks [348][349][350][351]. The biocompatibility of microfluidic systems based on other materials such as silicon oxide, PDMS and glass were investigated, and all showed good cell viability [347].…”
Section: Biocompatibility and Cell Viability Within Microfluidic Systemsmentioning
confidence: 99%
“…Davidsson et al 51 investigated the effect of paracrine diffusion distances and stress in their microfluidic cellular analysis device. The investigators created a microfluidic system that allowed long-term cellular analysis in sterile conditions while also minimizing the stress imposed on the cell.…”
Section: Experimental Platforms For Cellular Analysis and Cellular Symentioning
confidence: 99%